Mandibular Reconstruction Following Central Giant Cell Granuloma Resection in Primary Dentition: A Case for the Use of a Costochondral Graft. (February 2021) - Khavanin, Nima; White, Marissa J.; Walsh, Jonathan M.; Steinberg, Jordan P.
Central giant cell granuloma is a benign, intraosseous lesion that may affect the pediatric craniofacial skeleton, particularly the mandible. When surgery is indicated, the role of the craniofacial surgeon is to ameliorate the sequelae of ablative surgery by restoring facial symmetry, ensuring appropriate postoperative occlusion, and allowing for adequate interincisal opening, all in the setting of a growing craniofacial skeleton. Herein, we report the case of a 3-year-old female presenting for reconstruction after resection of the right hemimandible proximal to the unerupted first permanent molar. We highlight the various reconstructive challenges associated with mandibular reconstruction during primary dentition and make a case for the use of a costochondral graft, with a successful outcome demonstrated at 2 years of follow-up.